Generation and Characterization of Anti-AA Amyloid-Specific Monoclonal Antibodies - Wall, Jonathan S.; Kennel, Stephen J.; Richey, Tina; Allen, Amy; Stuckey, Alan; Weiss, Deborah T.; Macy, Sallie D.; Barbour, Robin; Seubert, Peter; Solomon, Alan; Schenk, Dale (Frontiers in Immunology, 2011)
AA amyloidosis results from the pathologic deposition in the kidneys and other organs of fibrils composed of N-terminal fragments of serum amyloid A protein (SAA). Given that there are only limited means to visualize these deposits, we have developed a series of mAbs, 2A4, 7D8, and 8G9, that bind specifically with nanomolar affinity to a carboxy-terminal epitope generated following proteolysis of SAA that yields the predominant component of AA amyloid deposits. Notably, these antibodies do not recognize native SAA, they retain their immunoreactivity when radiolabeled with I-125 and, after injection into AA amyloidotic mice, localize, as evidenced by autoradiography and microSPECT imaging, to histologically confirmed areas of amyloid deposition; namely, spleen, liver, and pancreas. The results of our in vitro and in vivo studies demonstrate the AA fibril-selectivity of mAbs 2A4, 7D8, and 8G9 and warrant further investigation into their role as novel diagnostic agents for patients with AA amyloidosis.